âCULTUREâ AS A SKILL IN UNDERGRADUATE EFL CLASSROOMS: THE BANGLADESHI REALITIES - Faheem Hasan Shahed (TEFLIN, 2013)
As regards the status of English in todayâs globalization era, âcul- tureâ has turned out to be an essential component in the teaching and learn- ing of English. Some Applied Linguists have even described it as the fifth skillâafter listening, speaking, reading and writingâwhich must be han- dled adequately in EFL classrooms. By appreciating and acquiring the cultural knowledge, values and skills associated with the different varieties of English, EFL students could develop their cultural sensitivities using English as the medium of instruction despite their resentment motivation. Eventually, students would be able to identify and respond to both culturally significant and inappropriate information and think positively about being a part of international environment. Given the growing importance of EFL teaching in Bangladesh, this study investigated the roles of âcultureâ in the under- graduate EFL classrooms. That is, the study carefully evaluated the effort and capabilities of the teachers in dealing with culturally sensitive issues in their materials, and the influences of cultural items of English on studentsâ learning. The study made constructive recommendations for English teachers to have successful implementation of cultural skills in their ELT activities regarding Bangladeshi socio-cultural realities which would make students become effective workforce in this challenging era.Â